Sa'yo and boto ko, kapwa!: A qualitative study on the content of parasocial relationships in Philippine politics - Say, Chloe Louise Chua (Animo Repository, 2022)
Since the proliferation of the internet and social media, many politicians have capitalized on the platforms by garnering a large following. Politicians have gone from picture-perfect commercials to real-life relatable tweets or videos to portray themselves to the public. This type of preferred intimate and relatable interaction can be seen as a parasocial relationship, wherein individuals form a side-one-sided relationship with media figures as if they are friends (Chung & Cho, 2017). This research aimed to analyze the contents and factors of parasocial relationships of Filipino voters to their preferred presidential candidates during the 2022 elections. Additionally, the study aimed to analyze how the content of parasocial relationships is seen through the lens of the Kapwa theory, specifically ibang tao and hindi ibang tao. To test the hypothesis, this study used the Political Parasocial Relationship Scale to test for the parasociality that the participants experienced with their desired presidential candidate. Out of the 420 participants, 12 participants were then contacted to be part of the focus group discussions and individual interviews to further identify the content of parasocial relationships. The sessions were then transcribed and analyzed using thematic analysis to identify the key themes and subthemes from the data collected. The results of this study resulted in four key themes namely (a) Exposure and intensification: Media influence on parasocial relationships, (b) Perceived similarities of the candidate to self and significant others, (c) Perceived closeness with the preferred presidential candidate, and (d) Looking at the candidate on a positive light. The findings of the study indicated that the hindi ibang tao concept is an important factor of parasocial relationships in the Philippine political context, congruent to the study’s framework. This study provides a cultural explanation of the dynamics between political candidates and Filipino voters through hindi ibang tao and how it affects their voting behavior. Keywords: Parasocial relationships, political context, relationships, Philippine politics